Determination of cytokeratins 1, 13 and 14 in oral lichen planus - Rivarola de Gutierrez, Emilce (2014)
Cytokeratins (CK) are molecules of the cytoskeleton that contribute to the cellular differenciation. We studied the expression of CK1, CK13 and CK14 in thirty-three patients with OLP. The biopsied lesions were located in the dorsal surface of the tongue, the palatal keratinized mucosa and the nonkeratinized buccal mucosa. Objectives: This study aimed to determine the expression of CK1, CK13 and CK14 in oral lichen planus (OLP) and its relations with: clinical patterns, prognosis, drugs and tobacco intake and histopathological features. Study Design: Immunohistochemical analysis, retrospective, descriptive, observational and no randomized study. Results: No significant difference was observed in the expression of CK1 in patients with or without drug treatment. No association was found with the amount of drugs intake or smoking nor with the histopathological features examined. Samples immunostained with CK13 were all positive in the suprabasal layers, and 13 of them in the basal layer. In these last ones, statistical analysis showed significance in the grade of vacuolization of the basal layer (p=0.023) and in the degree of exocytosis (p=0.0025), this, making the degree of affection higher for both parameters. Thirty-two tissue sections were immunostained with CK14. CK14 was expressed in the basal layer in 97% of samples and in the suprabasal layer in 94% of samples. Conclusions: The three CK were altered in OLP. CK1 does not have a direct connection with the presence of orthokeratosis. The finding of the CK13 in the basal layer is related to the agression of the lymphocytic infiltration in the epithelium, due to the basal stratum vacuolization and the increase in lymphocytic exocitosis. The presence of CK14 in the suprabasal stratums is not a parameter to predict malignancy. The CK in OLP do not follow the normal pattern of keratinized or non-keratinized mucosa.